Οι τίτλοι των μυθιστορημάτων: Θεωρητικό – ερμηνευτικό σχήμα και παραδειγματική εφαρμογή - Τσούπρου, Σταυρούλα (Σύγκριση/Comparaison/Comparison, 2012)
Leo Hoek in his semeiotic analysis of titles offers a functional interpretative scheme for the title of the novel in general. According to this, the semeiotic relations that are developed and concern the title include the following elements: 1. The sum of the linguistic signs / the Syntax of the title. 2. The sum of the abstract mental representations provoked by the aforesaid / the Semantics (Sémantique)or the Semasiology of the title. 3. The sum of the objects to which these mental representations refer / the Sigmatics (Sigmatique) of the title. 4. The sum of the individuals who transmit or comprehend the aforesaid linguistic signs / the Pragmatics (Pragmatique) or Pragmatology of the title (these relations are certainly not independent of one another). The analysis of titles presented here combines Hoek’s semeiotic analysis with Genette’s conclusions on the paratextual functions of the title, in order to clarify the relations between the ‘saying’ and the ‘doing’ of each specific title, that is to clarify what each title does, how and why it does it.